A prospective observational study to evaluate potential drug-drug interactions in patients admitted in intensive care unit, at BRIMS tertiary care hospital in Bidar, India - Singh, Shailander; K., Swetha (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Drug interaction occurs when presence of one drug affects the activity of another when, both are co-administered. 6-30% of adverse events (AEs) with significant hospitalizations or death are by drug-drug interactions(DDI). There is increased possibility to prevent the potential drug-drug interactions (pDDIs), if their prevalence and pattern are determined accurately before their occurrence. Hence this study aimed to evaluate the prevalence of pDDIs in ICU patients at BRIMS tertiary care hospital, Bidar. Methods: This prospective observational study included 30 patients admitted in ICU of BRIMS hospital for >24hrs of either gender, aged >18yrs. The study was conducted for a period of 3 months. Data was collected from the case records of patients on the predesigned proforma. Potential drug-drug interactions were classified based on their severity and the risk of Potential drug-drug interactions was estimated by Lexicomp, inc.version; 3.0.1.drug interact android mobile application. Results: Out of 35 patients admitted in the ICU, 30 cases were included in the study. The mean age of study population was 56.3years. The study population was exposed to a total of 330 medicines during the hospital stay with an average of 11.7 drugs per patient. The prevalence of pDDI was 93.3% (28) with an average of 9.75 pDDI per patient. According to Lexicomp drug interact android mobile application majority (63%) of pDDI were found to be moderate in their severity, 67% belonged to type C risk. Conclusions: The study showed higher prevalence of pDDI among ICU patients due to the complexity of the pharmacotherapies administered.